Fracturing effects evaluation and gas water production characteristics analysis at different layers of surface horizontal wells - Mingqiang LI; Chunhui YE; Tengfei CAO; Ke YANG; Zhainan ZHANG; Wenjie LIU (Meikuang Anquan, 2025)
To achieve a refined evaluation of the effect of hydraulic fracturing in surface horizontal wells, the characteristics of the drilling construction layers of the U1 and U2 horizontal sections in Zhujidong Coal Mine were analyzed. The fracturing effects of different layers in each section of the U1 and U2 wells were compared and analyzed from the perspectives of fracturing construction scale, fracturing construction curves, and pressure falloff data. Based on micro-seismic monitoring, the differences in the fracturing effects of the U1 and U2 wells were analyzed from the perspectives of the plane and height parameters of the fracture network and the types of fractures. A technical method for evaluating the effect of hydraulic fracturing in surface horizontal wells was initially formed by combining fracturing construction parameters with micro-seismic monitoring results. Finally, the drainage effects of coalbed methane in the U1 and U2 wells were compared and analyzed. The results showed that the total liquid volume, total sand volume, liquid volume per meter, and sand volume per meter in the U1 well were all lower than those in the U2 well. The number of good fracturing sections in the U1 well was only 8, which was less than the 10 in the U2 well, and the overall curve was mainly stable. The pressure fluctuation of the pressure falloff in the U1 well was greater than that in the U2 well, and the fracturing effect of the U2 well was better than that of the U1 well. From the perspective of fracturing data at different layers, the average fracturing liquid volume of the roof and floor in the U1 well was larger than that of the coal seam, and the amount of sand in the stage is relatively small, but the overall difference was not significant. In the U2 well, both the fracturing liquid volume and the fracturing sand volume of the roof and floor were lower than those of the coal seam fracturing. The stable curves of the roof and floor fracturing in both the U1 and U2 wells were less than those of the coal seam fracturing. The pressure falloff data of the roof and floor fracturing in the U1 well were greater than those of the coal seam fracturing, while the U2 well was the opposite. In most cases, the fracture network opening effect of the coal seam fracturing was better than that of the roof and floor. The plane parameters of the fracturing fracture area were more discrete, but the fracturing effect could be better verified and evaluated from the perspectives of fracture height and fracture type. The current gas and water production patterns of the U1 and U2 wells both included the drainage phase, the production increase phase, and the stable production phase. From the perspective of each phase and the overall gas and water production pattern, the gas production effect of the U2 well was better than that of the U1 well, which was consistent “the fracturing effect of the U2 well was better than that of the U1 well”.